Strategi Coping Stres Mahasiswa Selama Pembelajaran Daring - Latifah Nur Fauzi; Sinta Ari Susanti; Melati K Wardani (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
During online learning in pandemic era, college students experience a lot of pressure, from inside and outside. The pressure factor from the inside is the pressure that is caused from the college students itself, while the pressure factor from the outside is the pressure that is exerted from the environment and other people. This pressure causes students to experience stress during learning. This study aims to find out the stress faced by college students and coping strategies used. Researchers used Narrative Inquiry (NI) with thematic analysis techniques. Participants in this study were five college students of IAIN Surakarta. Data collection used semi-structured interviews consisting of two stages. The results shows that students experience stress both of pressure factors from inside and outside. Coping strategies used are two coping strategies that focused on problems and coping strategies that focused on emotions. This research can contribute to education, especially college students who experience stress can choose coping strategies that appropriate with themselves and for lecturers can evaluate learning strategies that understand the condition of college students in order to achieve the desired learning objective.